An evaluation of urbanization processes in suburban zones with the use of land cover data and the fuzzy set theory - Cieślak, Iwona; Górecka, Kamila (Bulletin of Geography. Socio-economic Series, 2021)
The aim of this article was to evaluate urbanization processes in space with the use of the CORINE Land Cover (CLC) databases. The study was conducted in the rural municipality of Dywity, located in the direct vicinity of the city of Olsztyn. Basic concepts and methods for evaluating urbanization processes were determined based on a review of the literature. The article addresses issues related to spatial management and GIS as a data source and a tool for analyzing land management activities. The search for new methods for evaluating spatial management and spatial processes plays a particularly important role in rapidly urbanizing areas. The study explored the applicability of GIS as a data source and a tool for evaluating urbanization processes in studies that rely on modern methods such as the fuzzy set theory. The intensity and dynamics of urbanization processes were evaluated based on changes in land cover with the use of CLC databases.